IMPACT OF IMPLEMENTATION OF THE EUROPEAN FOUNDATION FOR QUALITY MANAGEMENT EXCELLENCE MODEL AND ISO ON ORGANIZATIONS` PERFORMANCE BASED ON MATHEMATICAL MODELS - Heydari, Mohammad; Lai, Kin Keung; Xiaohu, Zhou (Proceedings of National Aviation University (archive), 2019)
In this paper, first some of the weaknesses of the EFQM model are studied, then with the usage of the structure of input-output governing of the model and using the Data Envelopment Analysis, a method is offered to recognize the lack of the proportion between Enablers and the results of organization which may occur due to problems and obstacles hidden in the heart of organization. In this study two window analysis of BCC and CCR with input nature were used to investigate the trend of performance changes in the Persian cutting industry during 2015.In this paper, Information has been obtained from individuals and groups through the use of survey research for decades, and the total reliability of the questionnaires was reported by using Cronbach’s alpha. Questionnaires used were »job satisfaction and organizational commitment with the reliability of 0.766«, »Job attachment questionnaire with reliability of 0.846«, »organizational climate questionnaire with the reliability of 0.960«. Studied population included 105 employees in the Persian cutting industry. Questionnaires were distributed randomly to the group,and finally, 67 questionnaires had been completed, and the analysis was once performed on 67 participants. The results confirmed that five factors such as » job satisfaction, organizational commitment, job attachment, job attitude and organizational climate «showed a significant difference before and after using the EFQM and ISO models. Organizational climate for the purpose of comparing the mean and standard deviation before and after the use of EFQM and ISO it was once referred to that it declined from (61.16) before implementation of these two models to (56.36) after implementation with a standard deviation of (11.63) and (9.66) after implementation of this models. Therefore, the relationship used to be reversed.